Novel Feedstocks for Biofuels Production - Guldhe, Abhishek; Singh, Bhaskar (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book critically evaluates recently investigated feedstock for biofuels production. Biofuel sector is rapidly evolving to cater the renewable energy demands. Novel and advanced feedstock are being investigated for their techno-economic feasibility. Environmental concerns, food vs fuel debate, energy security, economic feasibility, and availability are the major drivers for exploring different feedstock for biofuel production. This book explores a wide range of potential biofuels feedstock, their functional concepts, recent advancement, novel technique and critical evaluation with other available biofuel feedstock. This book also discusses future prospects of biofuel production. It is a useful read for students, researchers, faculty, industry and policy makers in the biofuel field.
1 Biofuel production from conventional feedstocks: Challenges and alternatives -- 2 Novel feedstocks for biofuels: Current scenario and recent advancements -- 3 Non-edible oil plants for biodiesel production -- 4 Role of Microorganisms in Production of Biofuels -- 5 Algal Biomass for Biodiesel and Bio-oil Production -- 6 Algae as a feedstock for bioethanol and biomethane production -- 7 Aquatic weeds as bioenergy feedstock -- 8 Wastewater and solid waste as feedstock for energy production -- 9 Agricultural lignocellulosic waste for bioethanol production -- 10 -- Food Wastes for Biofuels Production -- 11 Animal Fats Derived Biodiesel and Nano-Technology Applications -- 12 Potential microorganisms for power generation via microbial fuel cells. .
Keywords: Microbiology; Refuse and refuse disposal; Environmental chemistry; Microbiology; Waste Management/Waste Technology; Environmental Chemistry